Evaluation of the Relationship of Low Back Pain with Spinal Anesthesia and its Related Factors in Patients Undergoing Urological Surgery - Tayyebi Azar, Ali; Mohammadi Aghjehghaleh, Shadieh; Karami, Tohid (Archives of Men's Health, 2023)
Background: Spinal anesthesia is the common method in outpatient surgeries, which has complications such as back pain. We aimed to evaluate the relationship between low back pain (LBP) with spinal anesthesia and its related factors in patients undergoing urological surgery. Materials and methods: In this cross-sectional study, 1000 patients undergoing urological surgery were enrolled. The severity of LBP was measured using the VAS (visual analog scale) pain on the 1st day, the 1st week, and the 1st month postoperatively. Patients’ age, sex, and the duration of surgery were collected. data analysis was performed using SPSS software, version 17. Results: Of the 1000 patients undergoing urological surgery, 636 (63.6%) patients and 364 (36.5%) patients underwent spinal and general anesthesia, respectively. In patients under general anesthesia, the LBP prevalence was higher than in patients under spinal anesthesia on the 1st week and the 1st month after surgery (P<0.05). So, the LBP prevalence was as follows: on the 1st day (general anesthesia: 14.5% vs spinal anesthesia: 24.1%, p=0.09), at the 1st week (general anesthesia: 24.9% vs spinal anesthesia:13.5%, P=0.001) and the1th month (general anesthesia: 13.8% vs spinal anesthesia: 4%, P=0.001). On 1st day and 1st week after surgery, the rate of LBP was significantly higher in the >45-year age group than in the age group less than 45 years (P<0.05). The pain rate was higher in patients who had surgery duration of more than 2.5 hours in all three time periods (P=0.001). Conclusion: Although the LBP prevalence on 1st day after surgery in patients undergoing urological surgeries under spinal anesthesia was higher than in patients who underwent general anesthesia, there was a significant decrease in pain levels during the first week and month following the surgery in patients under spinal anesthesia. Older age and longer duration of surgery were related factors to pain.